Editorial Board - Makinde, Peter Oyewole (WritingThreeSixty, 2024)
Peter Oyewole Makinde - Editor in Chief Epie Bernadette Munge (Copy Editor i.) Amber Poggenpoel (Copy Editor ii.) Zuleika Shaik (Production Editor) Amber Small (Assistant Production Editor) Keanu Caden Morris (Academic Content Manager) Tatum Davis (Creative Content Manager) Laeeqah Ebrahim (Assistant) Quasiema Hendricks (Social Media Manager & Secretary)